2020
DOI: 10.5937/ekopolj2004087v
|View full text |Cite
|
Sign up to set email alerts
|

Descriptive statistics in corporate management and employee engagement in rural destinations

Abstract: Organizations that hope to achieve a competitive advantage through employee engagement will be most successful by incorporating and including employee engagement in the performance management process. Therefore, essence of the performance management must to be convergence to employees and establish communication with each one. The aim of this study was to determine the relationship between employee engagement (assessment of employee competencies and preferences of the engagement mechanisms), and performance ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…One of those aspects is both attractive and very dynamic workplaces. Working with people is exactly that: dynamic and attractive (Vunjak et al, 2020). Table 8 shows the respondents' agreement with that statement.…”
Section: Resultsmentioning
confidence: 95%
“…One of those aspects is both attractive and very dynamic workplaces. Working with people is exactly that: dynamic and attractive (Vunjak et al, 2020). Table 8 shows the respondents' agreement with that statement.…”
Section: Resultsmentioning
confidence: 95%
“…Many commentators (e.g. Hung-Lee &Haun-Jan, 2019; Vujko et al 2019;Vunjak et al 2020) have suggested that this balance of residents' perceptions of the costs and benefits of tourism is a major factor in visitor satisfaction and is, therefore, vital for the success of the tourism industry.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Tourism is one of the world's largest economic sectors, its importance to the global economy is undeniable, and it has been an important contributor to the United Nation's Sustainable Development Goals (SDGs) [2]. Tourism, as practiced in developed countries, is essentially an economic endeavor; whereas, in developing countries it is mainly developed as leisure consumption [3,4]. Pablo-Romero and Molina [5] concluded, in their literature review about the relationship between tourism and economic growth since 2002, that it is inconclusive and certainly open to discussion; however, there is evidence of a bidirectional causality, both in the short term and long term [6].…”
Section: Introductionmentioning
confidence: 99%